OS LIMES RENO-DANUBIANO: CONCEITO E PRÁTICA NO ALTO IMPÉRIO - Mendes, Norma Musco (PHOÎNIX, 2020)
The purposes of this paper are to discuss the maintenance of the ideology of imperi um sine line along of the Roman Empire and the roman concept of frontier, specifically in the West.